Reformist Narrative in Tafsir Al-Azhar - Sirajuddin Bariqi (SUHUF, 2025)
Abstract This article examines Hamka’s interpretation in Tafsir Al-Azhar regarding the death of Prophet Jesus (ʿIsa), a theological issue that has sparked considerable debate among Qur’anic exegetes and carries significant eschatological implications in Islam. Unlike the majority of classical tafsir which asserts that Jesus has not yet died, Hamka argues that he has indeed passed away. This study employs a qualitative approach through library research, with Tafsir Al-Azhar as the primary source, contextualized with the reformist thought of figures such as Muhammad ‘Abduh, Rasyid Rida, Ahmad Mustafa al-Maragiy, and Mahmud Syaltut. The findings reveal that Hamka’s interpretation not only reflects the influence of Islamic reformism but also demonstrates his independent exegetical effort to construct a contextual meaning. This is evident in three interpretive strategies: distancing his view from the Ahmadiyya despite a shared belief in Jesus’ death, engaging the Gospel as a counter-narrative to Christian theology, and incorporating Indonesia’s socio-religious context into his exegesis. Hamka’s tafsir illustrates his commitment to purifying Islamic doctrine and liberating Muslims from theological understandings he deemed unproductive.